(untitled) (Research, Society and Development, 2022)
Playful strategies contribute to dynamic and meaningful learning by arousing students’ interest and attention in a relaxed way. Therefore, this study aimed to identify the contributions of the didactic game “blood that saves”, associated with the expositive class, for the teaching of Science to 8th grade students of public school in Santarém-PA. The chosen topic, according to the teaching plan, was “Blood types, Rh factor and immune system”. Before the theoretical and recreational activities, a pre-test was applied to probe the students’ previous knowledge about the themes and, soon after, the theoretical class was applied. Then, the game was applied to 23 students from two classes (A and B) of the 8th year of elementary school. After the didactic game, a post-test was applied in order to verify the contribution of the playful activity, associated with the theoretical class, in the learning process. The game was played in pairs, each pair received a card that represented a full blood bag. According to the methodology and rules of the game, the pairs should assess the occurrence of the possibility of blood transfusions. The results obtained by analyzing the tests before and after the theoretical and recreational activities were satisfactory. There was a percentage increase in the average grades of the post-test in relation to the pre-test in both classes, in class A the increase was 35% and in class B, 42.65%. The playful strategy "blood that saves" provided a space for interaction and learning for students, enabling the construction of knowledge and thus contributing to the teaching and learning process, as well as to the development of skills, in addition to making the educational process more interesting and fun.